Proteolytic profiles of two isoforms of human AMBN expressed in E. coli by MMP-20 and KLK-4 proteases - Vetyskova, Veronika; Hubalek, Martin; Sulc, Josef; Prochazka, Jan; Vondrasek, Jiri; Vydra Bousova, Kristyna (Heliyon, 2024)
Ameloblastin is a protein in biomineralization of tooth enamel. However recent results indicate that this is probably not its only role in an organism. Enamel matrix formation represents a complex process enabled via specific crosslinking of two proteins - the most abundant amelogenin and the ameloblastin (AMBN). The human AMBN (hAMBN) gene possesses 13 protein coding exons with alternatively spliced transcripts and the longest isoform about 447 amino acid residues. It has been described that AMBN molecules in vitro assemble into oligomers via a sequence encoded by exon 5. Enamel is formed by the processing of enamel proteins by two specific proteases - enamelysin (MMP-20) and kallikrein 4 (KLK-4). The scaffold made of AMEL and non-amelogenin proteins is cleaved and removed from the developed tooth enamel. The hAMBN is expressed in two isoforms (ISO I and II), which could lead to their different utilization determined by distinct proteolytic profiles. In this study, we compared proteolytic profiles of both isoforms of hAMBN expressed in E. coli after proteolysis by MMP-20, KLK-4, and their 1:2 mixture. Proteolysis products were analysed and cleavage sites were identified by mass spectrometry. The proteolytic profiles of two AMBN isoforms showed different results, although we have to determine that the analysed AMBN was not post-translationally modified as expressed in prokaryotic cells. These results may lead to the suggestion of potentially divergent roles of AMBN isoforms cleavage products in various cell signalling pathways such as calcium buffering or signalling cascades.
Keywords: Ameloblastin; KLK-4; MMP-20; Enzymatic cleavage products; Proteolytic analysis